Simultaneous observation of collagen and elastin in normal and pathological tissues: analysis of Sirius-red-stained sections by fluorescence microscopy - Borges, L. F.; Taboga, SR; Gutierrez, P. S. (Springer, 2005)
In order to observe collagen and elastic fibers simultaneously, sections of human aorta, skin, lung, liver, and bladder were stained by Sirius red and analyzed by fluorescence microscopy. In all cases, the fibers of collagen presented the characteristic fluorescent red-orange color that results from the interaction of this extracellular protein with the dye, whereas elastic fibers showed strong green fluorescence (intrinsic fluorescence). This method efficiently detects collagen and elastic fibers when these two structures are present and could have valuable applications in processes that involves both fibers.
Keywords: collagen; elastin; Sirius red; fluorescence; human